Pengaruh Kualitas Produk dan Harga Terhadap Keputusan Pembelian Produk Face Wash - Fiqri Alief Fahrijal; Halimah Zahrah (Indo Publishing, 2026)
The increasingly intense competition in the facial skincare industry in Indonesia encour- ages consumers to be more selective in making purchasing decisions, particularly for face wash products such as Garnier. This study aims to analyze the effect of product quality and price on purchasing decisions of Garnier face wash. The research employs a quantitative approach with an explanatory design, using data collected through questionnaires distrib- uted to 100 respondents who are users of Garnier face wash, and analyzed using multiple linear regression. The results indicate that product quality has a positive and significant effect on purchasing decisions, while price also has a positive and significant effect as a supporting factor. Simultaneously, product quality and price are proven to influence con- sumers’ purchasing decisions. The conclusion of this study shows that consumers’ purchas- ing decisions are primarily driven by their perceptions of product quality, with price serv- ing as a reinforcing factor. Therefore, the findings of this study can be used as a consider- ation for companies in improving product quality and determining appropriate pricing strategies, as well as a reference for future research.